Teaching styles of faculty of education teachers at uptc in pedagogical and research projects i & ii (2015)
This article presents the findings of the research ‘Teaching Styles of Teachers at UPTC’, whose objective was to describe and characterize the teaching styles of teachers from the Faculty of Education at the Universidad Pedagógica y Tecnológica de Colombia, when developing the Research Educational Projects I &amp, II -subjects of the interdisciplinary area. The research was descriptive qualitative however quantitative data were also used in the application of tools for the characterization. This formative experience was based on sample teachers’ reflection and self-reflection about their knowledge and teaching practices, eleven teachers voluntarily joined the project whose target population consisted of twenty two. Methodologically speaking, some strategies and techniques such as direct classroom observation, video-lessons recordings consented by teachers, category questionnaires oriented to the teachers participating in the research and to the students of the twelve groups taking these subjects were used. Keeping in mind Callejas’ (2005) four dimensions -knowledge, know-how, know to communicate, and know how to be-, three teaching styles dominated: the critical, the technical, and the practical, the first prevailed and the others were found in a lesser degree.